Silica coated high performance oxide ceramics promote greater ossification than titanium implants: an in vivo study - Migliorini, Filippo; Schenker, Hanno; Betsch, Marcel; Maffulli, Nicola; Tingart, Markus; Hildebrand, Frank; Lecouturier, Sophie; Rath, Björn; Eschweiler, Jörg (Journal of Orthopaedic Surgery and Research, 2023)
Background: This in vitro study investigated the osseointegration and implant integration of high performance oxide ceramics (HPOC) compared to titanium implants in rabbits. Methods: Histomorphometry was conducted around the distal, proximal, medial, and lateral aspects of the HPOC to quantify the amount of mature and immature ossification within the bone interface. Histomorphometry was conducted by a trained musculoskeletal pathologist. The region of interest (ROI) represented the percentage of surrounding area of the implant. The percentage of ROI covered by osteoid implant contact (OIC) and mature bone implant contact (BIC) were assessed. The surrounding presence of bone resorption, necrosis, and/or inflammation were quantitatively investigated. Results: All 34 rabbits survived the 6- and 12-week experimental period. All HPOC implants remained in situ. The mean weight difference from baseline was + 647.7 mg (P < 0.0001). The overall OIC of the ceramic group was greater at 6 weeks compared to the titanium implants (P = 0.003). The other endpoints of interest were similar between the two implants at all follow-up points. No difference was found in BIC at 6- and 12-weeks follow-up. No bone necrosis, resorption, or inflammation were observed. Conclusion: HPOC implants demonstrated a greater osteoid implant contact at 6 weeks compared to the titanium implants, with no difference found at 12 weeks. The percentage of bone implant contact of HPOC implants was similar to that promoted by titanium implants.
CRIS-Team Scopus Importer:2023-01-20
Keywords: High performance oxide ceramics; Implantology; Ossification